Proteolytic Capability of Staphylococcus xylosus and Candida zeylanoides Isolated from Chinese Xuanwei Ham - Huang, Aixiang; Sirisansaneeyakul, Sarote; Chen, Zongdao; Wu, Zhixia; Chisti, Yusuf (Agriculture and Natural Resources, 2012)
The bacterium Staphylococcus xylosus and the yeast Candida zeylanoides, originally isolated from dry-cured Chinese Xuanwei ham, were investigated for proteolytic activity towards myoﬁ brillar protein extracts of fresh and salted semimembranosus muscle of pork. Both microorganisms were proteolytically active and caused progressive generation of shorter peptides and free amino acids through the hydrolysis of myoﬁ brillar proteins, which were analyzed by gel electrophoresis (SDS-PAGE)/a highperformance liquid chromatography and an automated amino acid analyzer, respectively. C. zeylanoides had a more pronounced proteolytic activity compared with S. xylosus. Hydrophilic peptides that have been associated with ﬂ avor development were detected in chromatograms of hydrolyzed samples of myoﬁ brillar proteins.